Meta-analysis of high-intensity interval training effects on cognitive function in older adults and cognitively impaired patients - Zhang, Wenting; Zeng, Shuyi; Nie, Yao; Xu, Keke; Zhang, Qiyuan; Qiu, Yu; Li, Yongqiang (Frontiers in Physiology, 2025)
BackgroundCognitive enhancement treatments are limited, and while High-Intensity Interval Training (HIIT) has been suggested to improve cognitive function, high-quality evidence remains scarce. This meta-analysis evaluates the effects of HIIT on cognitive performance compared to moderate-intensity continuous training (MICT) and control groups in older adults and cognitively Impaired Patients.MethodsA systematic search of PubMed, Embase, and Cochrane Library databases was conducted for articles published until 10 October 2024. Eighteen studies were included, comparing cognitive outcomes across HIIT, MICT, and control groups. Cognitive tests evaluated included the Stroop test, Digit Span Test (DST), Trail Making Test (TMT), and the MOST test.ResultsHIIT significantly improved performance compared to MICT in the Stroop test (SMD = −0.8, 95% CI: −1.3 to −0.2) and DST (SMD = 0.3, 95% CI: −0.0–0.5). Compared to control groups, HIIT significantly enhanced performance in the TMT (SMD = −0.7, 95% CI: −1.3 to 0.0) and MOST test (SMD = −1.2, 95% CI: −1.8 to −0.7).ConclusionThis meta-analysis supports the efficacy of HIIT in enhancing cognitive functions, particularly in cognitive flexibility, working memory, task switching, attention control, and inhibitory control. These findings suggest that HIIT can be an effective intervention for improving cognitive behavior in older adults and cognitively Impaired Patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, Identifier CRD42023413879.